PENERAPAN MODEL BLENDED LEARNING DALAM PEMBELAJARAN MATERI BENTUK ALJABAR DI KELAS VII SMP NEGERI 4 TOMOHON - Angelin Adeleyda Nangon; Ichdar Domu; Patricia V.J. Runtu (CV. ADIBA AISHA AMIRA, 2023)
This research is motivated by the results of observations found in the pandemic era, namely that there are still many educators who have difficulty in carrying out the teaching and learning process, which is caused by the limited face-to-face learning process where some learning is done online, thus making educators have to be careful in choosing learning models. to increase students' willingness to learn. This study aims to examine whether the learning outcomes of students who are taught using the Blended Learning model are higher than the learning outcomes of students who are taught using direct learning on algebraic forms of material. This research is in the form of an experiment with a quasi-experimental type and the design used in this study is the Posttest Only Control Group Design. The sample is part of the population. The sample of this study was taken 2 classes randomly, namely class VII B as the experimental class applied the Blended Learning model and class VII A as the control class using direct learning. The results of the study were analyzed using a t-test with a significance level of 0.05 is indicated by the calculated 7.191967906 > Ttable=2.009575237 so that H0 is rejected and H1 is accepted. Thus, it can be concluded that the application of the Blended Learning model affects student learning outcomes in algebraic forms of material.